The Role Of School Principals In Encouraging The Implementation Of The Strategy (Contextual Teaching Learning/Ctl) In Ipas Subjects At Sdi Dantar - Robertus Hudin; Alfonsus Sam; Erna Mena Niman; Emilia Mitasari (Syntax Corporation Indonesia, 2026)
This study was motivated by the importance of the principal's role in improving the quality of learning through the implementation of the Contextual Teaching and Learning (CTL) strategy in the IPAS subject at elementary school. describing the implementation of CTL, The purpose of this study was to describe the principal's role, and the supporting and inhibiting factors in its implementation at SDI Dantar. This study used a qualitative descriptive method. Data were collected through observation, interviews, and documentation. Data analysis employed the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. The results of the study showed that: (1) the principal played roles as educator, manager, supervisor, motivator, and facilitator through academic supervision, motivation, provision of facilities, and teacher professional development; (2) the implementation of CTL was carried out by connecting learning materials with real-life situations, group discussions, question-and-answer activities, environmental observations, and reflection; (3) supporting factors included the principal's support, teacher cooperation, a conducive school environment, and students' enthusiasm, while inhibiting factors included limited facilities, teachers' lack of understanding, limited time, and differences in students' abilities. It can be concluded that the principal's role is very important in encouraging the successful implementation of CTL so that learning becomes more active, meaningful, and in accordance with students' needs.